2013
DOI: 10.1016/j.tins.2013.10.001
|View full text |Cite|
|
Sign up to set email alerts
|

Manipulating sleep spindles – expanding views on sleep, memory, and disease

Abstract: Abstract:Sleep spindles are distinctive electroencephalographic (EEG) oscillations emerging during non-rapid-eye-movement sleep (NREMS) that have been implicated in multiple brain functions, including sleep quality, sensory gating, learning and memory. Despite considerable knowledge about the mechanisms underlying these neuronal rhythms, their function remains poorly understood and current views are largely based on correlational evidence. Here, we review recent studies in humans and rodents that have begun to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 128 publications
2
114
0
Order By: Relevance
“…While the Ca 2+ spike is readily observable in intracellular recordings, a burst is inferred in extracellular recordings using criteria that capture their intracellular statistics (100msec silence followed by <4msec interspike intervals) [43] (Fig 2B). Thalamic Ca 2+ spikes are generated by low-threshold T-type Ca 2+ channels (CaV 3 family) [44], which are recruited at hyperpolarized membrane potentials that are thought to be more prevalent during periods of behavioral quiescence and sleep [45]. For the TRN, this would mean enhanced bursting during these states resulting in more widespread and longer-lasting inhibition of thalamic targets.…”
Section: The Thalamic Reticular Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…While the Ca 2+ spike is readily observable in intracellular recordings, a burst is inferred in extracellular recordings using criteria that capture their intracellular statistics (100msec silence followed by <4msec interspike intervals) [43] (Fig 2B). Thalamic Ca 2+ spikes are generated by low-threshold T-type Ca 2+ channels (CaV 3 family) [44], which are recruited at hyperpolarized membrane potentials that are thought to be more prevalent during periods of behavioral quiescence and sleep [45]. For the TRN, this would mean enhanced bursting during these states resulting in more widespread and longer-lasting inhibition of thalamic targets.…”
Section: The Thalamic Reticular Nucleusmentioning
confidence: 99%
“…Spindles are 7–14Hz phasic transients that are observed in the cortical electroencephalograph (EEG) during sleep, and have been linked to sensory processing and memory consolidation [45]. Spindles are known to require interactions between TRN and connected thalamus, but the detailed synaptic interactions have only been revealed recently.…”
Section: The Thalamic Reticular Nucleusmentioning
confidence: 99%
“…Sleep spindles, which originate in the thalamus and propagate to widespread cortical regions (De Gennaro & Ferrara, 2003), are robustly associated with offline memory processes (Astori, Wimmer, & Lüthi, 2013;Diekelmann, 2014;Rasch & Born, 2013). Human studies have reported increased spindle activity after learning (Gais, Molle, Helms, & Born, 2002;Schmidt et al 2006), as well as predictive relationships between spindle activity and subsequent memory performance; an effect observed across naturally occurring sleep (Clemens, Fabo, & Halasz, 2005;Schabus et al, 2004) and following pharmacological manipulations of spindle density .…”
Section: Sleep Spindles and Emotional Contextsmentioning
confidence: 99%
“…Spindle activity is modifiable24252627 and could represent an attractive therapeutic target if causally implicated in disease risk. In light of recent progress in schizophrenia genetics2829, genetically characterizing variation in spindle activity could help to elucidate pathways between genetic risk and neuropsychiatric disease23.…”
mentioning
confidence: 99%